The Jungle Book - Kipling, Rudyard, 1865-1936 (Salt Lake City, UT : Project Gutenberg, 2011)
"The Jungle Book" by Rudyard Kipling is a collection of stories published in 1894. The tales follow Mowgli, a boy raised by wolves in the Indian jungle, alongside animal characters like Shere Khan the tiger and Baloo the bear. Through these fables, Kipling explores themes of abandonment and belonging, law and freedom, teaching lessons about respect for authority while celebrating the wildness of nature. The stories blend human archetypes with animal forms, creating timeless tales that have captivated readers and inspired countless adaptations. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Jungle_Book
There is an improved edition of this title, eBook #236
Release date is 2011-04-30
Suzanne Shell, Ernest Schaal, and the Online Distributed Proofreading Team
Keywords: Short stories; Animals -- Fiction; Jungles -- Fiction; India -- Fiction; Jungle animals -- Fiction; Mowgli (Fictitious character) -- Fiction; Adventure stories, English; Feral children -- Fiction; India -- History -- 19th century -- Fiction